Hagiografía y método prosopográfico. A propósito de las Acta Martyrum - Bravo, G. (Antigüedad y Cristianismo, 1990)
The object of this paper has been to set limits to the traditional relation between the hagiography and prosopographical method. Here the used documents are the so-called ACTA MARTYRUM, which naturally contain some doubtful facts such as names of persons and cities, dates, etc. But this does not mean that all the data should be rejected just because not all of the persons or events mentioned are not historically accurate. The results are based on twenty of these documents, which seem to present less historical errors.